2017
DOI: 10.29063/ajrh2017/v21i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants used during Antenatal Care by Pregnant Women in Eastern Uganda

Abstract: Plants are commonly used during the antenatal stage in pregnancy to manage different ailments in Africa. In Uganda, both medicinal and food plants are used to handle common pregnancy related conditions. An ethnobotanical survey was conducted in Iganga district, eastern Uganda. Seven traditional birth attendants (TBA) and 46 mothers were interviewed. Data was collected using structured questionnaires and household interviews. The TBAs were identified using snowball sampling. A total of 33 plant species, belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…The dominance of these families is mainly due to some special properties, such as secondary metabolites. This illustration was observed with some differences discovered in other ethnomedicinal surveys conducted in other regions of the country [13,14] or worldwide [15] The…”
Section: Results and Discusion : Diversity Of Medicinal Plant Speciessupporting
confidence: 69%
See 2 more Smart Citations
“…The dominance of these families is mainly due to some special properties, such as secondary metabolites. This illustration was observed with some differences discovered in other ethnomedicinal surveys conducted in other regions of the country [13,14] or worldwide [15] The…”
Section: Results and Discusion : Diversity Of Medicinal Plant Speciessupporting
confidence: 69%
“…Curcuma alba L. and Drymoglossum piloselloides (L.) C. Presl was each used for the treatment of three diseases. Additionally, similar studies were reported from different part of Indonesia [14,30] or Worldwide.…”
Section: Maternal Health Ailment Treated By Traditional Medicinal Plantssupporting
confidence: 78%
See 1 more Smart Citation
“…Local herbs may be taken via the oral route in which they are most often consumed as a strong tea or chewed; rectal or vaginal routes and sometimes rubbing on the pregnant abdomen [14,15]. Herbal remedies may also be used to protect the fetus from evil in-vitro [16] and to have a healthy child [17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high proportions (23%) of women in Tanzania use herbal medicines during pregnancy and in inducing labour [6]. The commonly used herbs include a wide variety of herbs such as ginger (Zingier o cinale), onions (Allium cepa) and Neem (Azadirachtaindica) Some of the reported reasons for using herbs during pregnancy and labour include incidents of nausea and vomiting, strengthening pregnancy and health of the woman and the fetus, ensuring positive pregnancy outcomes and easing labour [6][7][8][9]. Others comprise of conviction that herbal medicines have the ability of inducing labour and shortening its duration, alleviating labour pains, enhancing removal of a retained placenta, as well as toning the uterine muscles post-delivery [5,10].…”
Section: Introductionmentioning
confidence: 99%